(untitled) (REVISTA NODO, 2024)
This project was imagined by STAR and BOARD shortly after completing “Co-Residence: Living Large”, a research project for the AIGP (Atelier International du Grand Paris) on the “maximization of space” through collaborative economy strategies, with the aim of proposing solutions to the housing crisis. At Cabanon, STAR and BOARD opted for a different strategy and experimented with “reduction.” The project was developed while STAR was designing the “Ilot-3H” in Ivry (Grand Paris), a large complex of 288 experimental homes.